Studies on Alkaline Serine Protease Produced by Bacillus clausii GMBE 22 - KAZAN, DİLEK (TAYLOR & FRANCIS INC, 2009)
An alkali tolerant Bacillus strain having extracellular serine alkaline protease activity was newly isolated from compost and identified as Bacillus clausii GMBE 22. An alkaline protease (AP22) was 4.66-fold purified in 51.5% yield from Bacillus clausii GMBE 22 by ethanol precipitation and DEAE-cellulose anion exchange chromatography. The purified enzyme was identified as serine protease by LC-ESI-MS analysis. Its complete inhibition by phenylmethanesulfonylfluoride (PMSF) also justified that it is a serine alkaline protease. The molecular weight of the enzyme is 25.4kDa. Optimal temperature and pH values are 60C and 12.0, respectively. The enzyme showed highest specificity to N-Suc-Ala-Ala-Pro-Phe-pNA. The Km and kcat values for hydrolysis of this substrate are 0.347mM and 1141min-1 respectively. The enzyme was affected by surface active agents to varying extents. The enzyme is stable for 2h at 30C and pH 10.5. AP22 is also stable for 5 days over the pH range 9.0-11.0 at room temperature. AP22 has good pH stability compared with the alkaline proteases belonging to other strains of Bacillus clausii reported in the literature.
Keywords: Alkaline protease; Bacillus clausii; Enzyme purification and characterisation; Serine protease; ALKALIPHILIC BACILLUS; PURIFICATION; SDS; OXIDANT; I-52; ALIGNMENT; GMBAE-42; STRAINS; ASSAY; HEAT